2020
DOI: 10.1111/1541-4337.12593
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advanced glycation end‐products: Perspectives linking food processing with health implications

Abstract: Dietary advanced glycation end products (dAGEs) are complex and heterogeneous compounds derived from nonenzymatic glycation reactions during industrial processing and home cooking. There is mounting evidence showing that dAGEs are closely associated with various chronic diseases, where the absorbed dAGEs fuel the biological AGEs pool to exhibit noxious effects on human health. Currently, due to the uncertain bioavailability and rapid renal clearance of dAGEs, the relationship between dAGEs and biological AGEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 195 publications
1
116
0
2
Order By: Relevance
“…AGEs are heterogeneous compounds derived from non-enzymatic glycation reactions from interactions between reducing sugars or oxidized lipids and proteins or nucleic acids. The pathological effects of AGEs are related to their ability to alter the chemical and functional properties of proteins and activate intracellular pathways promoting oxidative stress [78,79]. Studies indicate the possible effect of dietary AGEs on inflammation and cardiometabolic dysfunction in adults and in the pediatric population [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…AGEs are heterogeneous compounds derived from non-enzymatic glycation reactions from interactions between reducing sugars or oxidized lipids and proteins or nucleic acids. The pathological effects of AGEs are related to their ability to alter the chemical and functional properties of proteins and activate intracellular pathways promoting oxidative stress [78,79]. Studies indicate the possible effect of dietary AGEs on inflammation and cardiometabolic dysfunction in adults and in the pediatric population [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…), and they contribute in altering cellular functioning [ 66 ]. Through the RAGEs receptor, they activate NFkB, a cellular mediator of inflammation [ 67 ], thus stimulating and supporting the inflammatory process.…”
Section: Polyphenols and Obesitymentioning
confidence: 99%
“…The major sources of AGEs are grilled meats, baked goods, dairy products and processed food in general: high circulating levels of them are linked to oxidative stress and inflammation, which promote aging [ 68 ]. Fruits, vegetables and whole grains appear to have less AGEs [ 67 ].…”
Section: Polyphenols and Obesitymentioning
confidence: 99%
“…Nonetheless, there is controversy on whether these reactive compounds could contribute to AGE burden, since other researchers have shown that dietary dicarbonyls are unlikely to directly contribute to the endogenous pool of these compounds [ 85 ]. It has also been suggested that high-fat diets induce in vivo dicarbonyl formation [ 85 , 86 ]. Therefore, the increased level of endogenous AGEs observed in in vivo studies offering a roasted, high-fat diet might be partially explained by the high-fat induced formation of dicarbonyl compounds.…”
Section: Mechanisms Of Cell/tissue Damage Induced By Agesmentioning
confidence: 99%